2017
DOI: 10.1128/aem.03478-16
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacteria To Stabilize Archaeological Iron

Abstract: Iron artifacts are common among the findings of archaeological excavations. The corrosion layer formed on these objects requires stabilization after their recovery, without which the destruction of the item due to physicochemical damage is likely. Current technologies for stabilizing the corrosion layer are lengthy and generate hazardous waste products. Therefore, there is a pressing need for an alternative method for stabilizing the corrosion layer on iron objects. The aim of this study was to evaluate an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Samples of 12.5 × 25 × 2-3 mm were obtained from a steel plate with a natural urban corrosion layer mainly composed of lepidocrocite and goethite [25,26]. The plate was exposed for about 10 years in an urban environment (Zürich, Switzerland).…”
Section: Description Of Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples of 12.5 × 25 × 2-3 mm were obtained from a steel plate with a natural urban corrosion layer mainly composed of lepidocrocite and goethite [25,26]. The plate was exposed for about 10 years in an urban environment (Zürich, Switzerland).…”
Section: Description Of Samplesmentioning
confidence: 99%
“…This bacterium was selected as it can use a variety of electron acceptors, especially halogenated organic compounds and metals [29,30]. In addition, a previous study revealed that this strain was able to reduce Fe 3+ -citrate in the presence of 0.2% and 0.3% NaCl, and that it was more efficient in terms of production of iron phosphates on the surface of corroded iron coupons [25,26]. Bacterial pre-incubation was performed in the dark at 30 • C under agitation in a standard mineral medium under anoxic conditions in 500 mL serum bottles, until reaching an optical density (OD600) of 0.1−0.15, as previously described [31].…”
Section: Bacterial Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Biocorrosion of iron and iron alloys (Schutz et al, 2015) Production of stable corrosion products via biogenic mineral precipitation (Cote et al, 2015;Comensoli et al, 2017)…”
Section: Iron Reductionmentioning
confidence: 99%